Evaluation of two community outreach forensic psychological services. Issue 4 (4th November 2014) - Ward, Max; Attwell, Pamela
Abstract : Purpose: – The purpose of this paper is to gauge service user' perspectives on the effectiveness of two community outreach forensic psychological services in London for people with personality disorder and serious mental illness who pose a risk of sexual and violent offending. Both services are guided by principles of the Good Lives Model and circles of support and accountability. Design/methodology/approach: – The research design was mixed qualitative and quantitative, incorporating thematic evaluation of semi-structured interviews with service users and a rating-scale constructed specifically for this purpose. Findings: – Outcomes suggest both services are broadly successful in achieving their aims to: first, enhance psychological well-being and general quality of life; second, promote links with other agencies and broader social inclusion; and third, monitor and manage risk of re-offending. Research limitations/implications: – However, there are limitations. Cause and effect cannot be inferred and outcomes are not generalizable to other contexts partly as a result of the small sample size. Another possible issue is that participants spoke favorably about their care through fear of being evaluated negatively or through fear of compromising the support they receive. To control for these and other possible confounding variables, further more rigorous research is required. Practical implications: – The current findings can be used as a guide to help services engage and manage people with personality disorder and serious mental illness who are at risk of further serious offending. Originality/value: – It is suggested here that the current findings contribute to the body of evidence supporting initiatives that aim to address recidivism by enabling offenders to develop a more positive identity through social and community inclusion and integration.